Model Matematika Pengendalian Penyebaran Penyakit Schistosomiasis Menggunakan Itik Sebagai Musuh Alami Bagi Keong Perantara Schistosomiasis - Karini, I; Ratianingsih, R (Program Studi Matematika, Universitas Tadulako, 2020)
In Indonesia Schistosomiasis is only found in Central Sulawesi Province, in the highlands of Lindu, the Napu plateau and the Bada plateau, Poso Regency. The disease is caused by the Schistosoma japonicum worm which requires an intermediary host, namely the Oncomelania hupensis lindoensis snail, which is an endemic animal in the area. This study examined mathematically the control of the spread of Schistosomiasis by using ducks as natural enemies for intermediate snails. The human population is divided into vulnerable human subpopulations and a subpopulation of infected humans. Interactions between snail populations and duck populations are expressed as interactions between Predator and Prey. The Schistosoma japonicum worm population is seen as a population growth cycle model. The stability of the model is analyzed using the Jacobi matrix, which is evaluated at a critical point. The model has two critical points ð‘‡1 and ð‘‡2 which represent a disease-free conditions, while ð‘‡3 represents endemic point. Mathematical model simulations controlling the spread of Schistosomiasis. The simulation is using ducks with early populations indicate that disease control by using ducks is less effective because it takes a very long time to be estimated at 55 years. Keywords : Conch Oncomelania Hupensis Lindoensis, Duck, Schistosomiasis, Schistosoma Japonicum Worm.